A study on the values reflected by space utilization and design of the dining area in the homes of selected low-income households - Dela Cruz, Rowena P.; Mayo, Adelaida Villaraza (2011.)
This study sought to determine the values reflected by the space utilization and design of the dining areas within the homes of selected low-income households. For purposes of this study, the dining area is defined as the space within the home where the family serves and consumes the three major meals of the day uch as breakfast, lunch and dinner. The sample included five (5) Filipino families who were randomly selected from a low-income community, Gawad Kalinga, located at Laura St., Barangay Matandang Balara, Commonwealth Ave., Quezon City. The data were gathered using descriptive research design and qualitative research method, which included instruments such as observation, photograph documentation and interview. results show that most of the respondent families use one common space is fluid and always bears the opportunity change of purpose or function. Furthermore, findings reveal that even though the dining area is not structured or typical - meaning having the usual layout of a dining table surrounded by dining chairs - there is a fixed setting arrangement being followed by each member of household; thus showing Filipino concept of territoriality. The use of space of the respondent families shows their pagkamatiisin (making do with what they have), pagkikipagkapwa (getting along with other members of the group), familism (being family-oriented and being a part of a group), and a Christian faith. The design and layout of the space unveil the Filipino' practicality and trait of pakitang-tao (showing what we deem valuable to get pleasing impression from others), which roots from our high regard on what is panloob (to hide) and panlabas (for show). The study recommends that more studies on the Filipino sense of space be conducted when designing especially for the improvement of space utilization within homes of low-income families.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Dining rooms -- Philippines